2019
DOI: 10.3390/rs11242960
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Spatiotemporal Variations of Sentinel-1 InSAR Coherence at Different Time Scales over the Atacama Desert (Chile) between 2015 and 2018

Abstract: This study investigates synthetic aperture radar (SAR) time series of the Sentinel-1 mission acquired over the Atacama Desert, Chile, between March 2015 and December 2018. The contribution analyzes temporal and spatial variations of Sentinel-1 interferometric SAR (InSAR) coherence and exemplarily illustrates factors that are responsible for observed signal differences. The analyses are based on long temporal baselines (365–1090 days) and temporally dense time series constructed with short temporal baselines (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 48 publications
(97 reference statements)
0
15
0
Order By: Relevance
“…With the installment of contemporary InSAR assets such as Terra SAR X, Advanced Land Observing Satellite (ALOS) Phased Array type L-band Synthetic Aperture Radar (PALSAR) 1/2, and Sentinel-1, which have better resolution, revisiting times, and resolving power on the baseline conditions, nowadays some research has begun to establish methods of monitoring sand dune dynamics and eolian migrations as shown in Gaber et al (2018), Gómez et al (2018), and Havivi et al (2018). A detailed study of phase coherence behaviors in arid deserts which may involve eolian erosions was reported by Ullmann et al (2019) who showed that surface characteristics such as slope and wetness are not crucial for the loss of phase coherence, the so-called decorrelation. Thus, the prime factor affecting decorrelation is the change of topography induced by eolian migrations.…”
Section: Methodsmentioning
confidence: 99%
“…With the installment of contemporary InSAR assets such as Terra SAR X, Advanced Land Observing Satellite (ALOS) Phased Array type L-band Synthetic Aperture Radar (PALSAR) 1/2, and Sentinel-1, which have better resolution, revisiting times, and resolving power on the baseline conditions, nowadays some research has begun to establish methods of monitoring sand dune dynamics and eolian migrations as shown in Gaber et al (2018), Gómez et al (2018), and Havivi et al (2018). A detailed study of phase coherence behaviors in arid deserts which may involve eolian erosions was reported by Ullmann et al (2019) who showed that surface characteristics such as slope and wetness are not crucial for the loss of phase coherence, the so-called decorrelation. Thus, the prime factor affecting decorrelation is the change of topography induced by eolian migrations.…”
Section: Methodsmentioning
confidence: 99%
“…The IW2 datasets were processed using the Sentinel applications platform (SNAP) software (version 7.0.2), IDL 8.7.2, and ENVI 5.5. A processing chain developed in preliminary work [7,41,42] was used to processes the terrain-corrected gamma nought VV (GVV) and VH (GVH) intensities (following the approach of [43], which is approximated as "Terrain-Flattening" function in SNAP). The TanDEM-X DEM (Section 2.2.3) with a pixel spacing of 12 by 12 m was used for the calibration, the terrain flattening, and the range-doppler terrain correction.…”
Section: Sentinel-1mentioning
confidence: 99%
“…Therefore, we consider an exponential model as appropriate, which is in accordance to results from other studies (e.g., [21]). Z value (ZVAL): The ZVAL relates the RMSH and CORL by the ratio shown in Equation (7). The intention of this parameter is to account for vertical and horizontal variations in a single index [30].…”
Section: Surface Roughness Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that gullies are dynamic features, behavioral indicators based on temporal patterns [i.e. Normalized Difference Vegetation Index (NDVI), radar coherence [58], and backscatter intensity time series] are included as gully descriptors. This is important in light of the fact that trends of historical data differ between adjacent areas [57], [59], [60].…”
Section: Introductionmentioning
confidence: 99%